The Microwave-assisted Synthesis of Polyethersulfone (PES) as A Matrix in Immobilization of Candida antarctica Lipase B (Cal-B) - Khusna Widhyahrini; Nurrahmi Handayani; Deana Wahyuningrum; Santi Nurbaiti; Cynthia Linaya Radiman (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2017)
Candida antarctica lipase B (Cal-B) has been widely used in the hydrolysis reaction. However, it has some weaknesses, such as: forming of the heavy emulsion during the process, which is difficult to resolve and has no reusability. Therefore, it needs to be immobilized into a suitable matrix. One of the suitable supporting materials is polyethersulfone (PES) and its synthesis becames the objective of this paper. The PES was synthesized via a polycondensation reaction between hydroquinone and 4,4'-dichlorodiphenylsulfonein N-methylpyrrolidone (NMP) as solvent using Microwave Assisted Organic Synthesis (MAOS) method at170 °C for 66 minutes using an irradiation power of 300 watt. The synthesized PES was characterized by FTIR and 1H-NMR (500 MHz, DMSO-d6). Then the PES membrane was prepared from 20 % of the optimized mixtures of PES, PSf (polysulfone), and PEG (polyethylene glycol) dissolved in 80 % NMP. The Cal-B was immobilized on the PES membrane by mixing it in a shaker at 30 °C and 100 rpm for 24 h using phosphate buffered saline (PBS). The identification of the immobilized Cal-B was done by using FTIR-ATR spectroscopy and SEM micrographs. The results of Lowry assay showed that the ‘Cal-B immobilized’ blended-membrane has a loading capacity of 91 mg/cm2 in a membrane surface area of 17.34 cm2. In this work, the activity of immobilized Cal-B was twice higher than the native enzyme in p-NP (p-Nitrophenolpalmitate) hydrolyzing. The results indicated that the synthesized PES showed a good performance when used as a matrix in the immobilization of Cal-B.